Hedging the investment portfolio with derivatives present on the Polish market - Tomasz Bernat; Robert Ruszkiewicz (Managerial Economics)
This paper explores the evolving nature of the capital market in the second and third decades of the 21st century, characterized by its widespread accessibility to individual investors. Howthe study investigates practical methods to minimize risk, focusing on the limited availability of derivatives in the Polish capital market. The research develops and tests an investment portfolio, drawing on Markowitz’s portfolio construction theory and Hull’s hedging strategy. The Polish conditions using available tools and strategies.